Le Domérien-Toarcien Inférieur De La Ride De Fert Elbir (Rides Sud-Rifaines, Maroc) - Erragragui, Mohamed; Masrour, Aïssa; Benbaqqal, Hicham; Gretaa, Mostafa (European Scientific Journal, ESJ, 2017)
The South-Rifain ridges are located at 30 Km in the North of Meknes City, they constitute the extreme southern limit of the Rifaine chain. Globally, these ridges integrate into the history of African northwestern margin evolution. Mainly, the frame of this ridge is composed of the Jurassic sedimentation. The Fert Elbir ridge, subject of this study, is among the leading reliefs in the South-Rifain ridges. Generally, in this ridge, two geological sections have been studied, in the objective to determine and to understand the history of sedimentological, bio-stratigraphical and paleoenvironmental evolution of the Jurassic sedimentary series. Essentially, it includes the carbonates and marls deposits, composed mainly by several facies and micro-facies, grouped in eight facies associations. They contain a very important biological diversity especially at the level of the middleDomerian. Paleo-environmentally, this sedimentation series was deposited in the many diversified environments, having the areas of deposit essentially very close to the coast (proximal), or located in distal position with several hundred meters from the shore.